The influence of social media marketing activities on consumer brand engagement, willingness to pay a premium price, purchase intentions - Panangian, Jonathan; Masnita, Yolanda (Institute of Computer Science (IOCS), 2024)
This research aims to investigate the influence of social media marketing activities on consumer brand engagement, willingness to pay premium prices, and purchase intentions. The sample selection technique used was purposive sampling involving 115 respondents. In addition, data analysis was carried out using AMOS software. In this research, social media marketing activities will be examined to see their impact on consumer brand engagement, willingness to pay premium prices, and purchase intentions. Purposive sampling is used as a sample selection technique, which allows researchers to select respondents who comply with previously established criteria. It is hoped that the results of this research will provide a better understanding of how social media marketing activities can influence consumers' brand engagement, willingness to pay premium prices, and purchase intentions. Apart from that, this research can also provide insight into the effectiveness of purposive sampling technique and the use of AMOS software in data analysis